IMPLEMENTATION OF BEHAVIOR APPROACHES IN LEARNING WRITING CERPEN THROUGH LITERATURE ENGINEERING IN IKIP SILIWANGI - Mimin Sahmini; Agus Priyanto (JLER (Journal of Language Education Research), 2019)
This research applies behavioristic learning theory in learning to write short stories with literary engineering. In this research it is expected that students will be skilled in writing short stories through literary engineering to foster imagination and ideas that will be written by students in short story writing activities. This research is based on the problem that a student has difficulty writing something that he feels and thinks in written form. Most students express their experiences more easily by speaking in terms of them, students rarely pour into written form. Another problem related to student creativity in writing activities is that many students who complain when getting a writing assignment from the lecturer are very annoying. This is because students do not know where to start and what to do in writing activities. Feelings of fear have become a scourge for students now in writing activities. This research method uses quantitative methods with experiments, in which researchers will provide implementation of the behavioristic approach in learning to write short stories with literary engineering. The results of this study indicate that students are more skilled at writing with literary engineering, where literary works in the form of poetry are changed by students in the form of short stories. As for the stages of each short story based on the experience of students both directly and indirectly into the short story. The learning process was very enjoyable and the students felt honed their talents and interests through this activity. An overflowing of feelings, hopes, and ideals is reflected in the writing of the students so that it helps the lecturer to hone the interests and talents of the students.